TEN YEARS EXPERIENCE IN MANAGEMENT OF BLADDER TRAUMA AT TERTIARY HOSPITAL IN WEST JAVA INDONESIA - Indra Firdaus, Gugum; Wijayanti, Zola; Mustafa, Akhmad; Adi, Kuncoro (Indonesian Urological Association, 2024)
Objective: The aim of this study is to provide the characteristics, management, and outcome of bladder trauma at the center of trauma referral hospital in West Java, Indonesia. Material & Methods: This is a retrospective and descriptive study. The data of bladder trauma were collected from the medical records from January 2010 to December 2019. The data were presented using descriptive statistics in frequency and percentage. Results: Over a ten-year period, there were 1,174 cases of urogenital trauma, with 170 cases (14.48%) involving bladder injuries. The majority of the was 21-30 years old and were men (55.88%). The most common cause was blunt abdominal trauma (68.82%), which was caused by traffic accidents (91.45%). With 42.24% pelvic fracture as the most common associated injury. The most common type of bladder injury (45.88%) was bladder contusion. Iatrogenic trauma was the second leading causes (29.42%) with obstetrics and gynecology operations accounted for 84% of iatrogenic bladder trauma cases. The majority of bladder injuries were identified using a computed tomography (CT) scan. In 59.41% of cases, surgical intervention was required. The mortality rate was 2.94% during post-operative treatment due to coexisting or associated multiple injuries. Conclusion: We discovered that bladder trauma most commonly affects males of reproductive age with blunt abdominal trauma as the most common etiology and pelvic fractures as the most common associated injury. Surgical intervention often was required. Keywords: Bladder injury, blunt abdominal trauma, iatrogenic bladder injury.